PENINGKATAN KEMAMPUAN MATEMATIS SISWA SMP AR-RAHMAN PERCUT MELALUI PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) - Rahayu, Riska (Universitas Samudra, 2023)
The aim of this study were to know (1) improved the abilities of students' mathematical communication who are taught by cooperative learning type STAD and who are taught by direct instruction and (2) interaction between student's mathematical initial abilities and learning models to improvement the abilities of students' mathematical communication. The type of research used in this study was quasi experimental with design of non-equivalent control group. The population in this study consisted of all students of grade VII SMP Ar-Rahman Percut amounting to 150 students, while the sample consisted of 30 students in class VII-B and 30 students in class VII-C. The research instruments used in this study were test of mathematical initial ability, pretest and posttest of mathematical communication ability, as well pretest and posttest of mathematical problem solving ability. Statistical hypothesis testing in this study using formula of ANOVA Two Way. The results showed that (1) improved the abilities of students' mathematical communication who are taught by cooperative learning type STAD higher than who are taught by direct instruction and (2) there was no interaction between student's mathematical initial abilities and learning models to improvement the abilities of students' mathematical communication.